2019
DOI: 10.3390/antiox8090336
|View full text |Cite
|
Sign up to set email alerts
|

Growth Performance and Characterization of Meat Quality of Broiler Chickens Supplemented with Betaine and Antioxidants under Cyclic Heat Stress

Abstract: Heat stress (HS) causes oxidative stress, which compromises broiler performance and meat quality. The aim of this study was to determine whether dietary antioxidants could be used as an amelioration strategy. Seventy-two day-old-male Ross-308 chicks were exposed to either thermoneutral or cyclical heat stress conditions. Diets were either control commercial diet (CON), CON plus betaine (BET), or with a combination of betaine, selenized yeast, and vitamin E (BET + AOX). Heat stress increased the rectal temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
59
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(80 citation statements)
references
References 81 publications
17
59
2
2
Order By: Relevance
“…Consistent with earlier experiments by our research group and others [2,5,37], betaine supplementation reduced respiration rate and rectal temperature, indicating partial amelioration of the effects of HS. Furthermore, betaine improved ileal villous height, area, crypt depth and seromuscular thickness.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Consistent with earlier experiments by our research group and others [2,5,37], betaine supplementation reduced respiration rate and rectal temperature, indicating partial amelioration of the effects of HS. Furthermore, betaine improved ileal villous height, area, crypt depth and seromuscular thickness.…”
Section: Discussionsupporting
confidence: 92%
“…Although the fractional oral bioavailability of betaine has not been quantified, it has been reported to be readily available [42], and in broilers has been reported to be absorbed in the jejunum [38]. In this experiment, betaine concentrations increased with supplementation in the ileum, kidney and spleen, and previously we observed that supplementation increases plasma, liver and muscle concentrations [2]. Elevated ileal betaine concentrations may be an indication of betaine absorption across a wider area of the GIT than previously thought, while the contribution of arterial second-pass betaine metabolism cannot be excluded.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Increase heart rate causes the release of catecholamines (adrenaline and nor‐adrenaline) from medullary tissues of adrenals during heat stress (Calefi, Quinteiro‐Filho, Ferreira, & Palermo‐Neto, 2017). Under stress conditions, the parabrachial nucleus is stimulated resulting in increment in respiration rate (Shakeri et al., 2019). Values recorded for respiratory rate in the three genotypes are similar to previous studies in broiler chickens under similar conditions (Abioja, Osinowo, Smith, & Eruvbetine, 2013).…”
Section: Discussionmentioning
confidence: 99%